Differential adaptation of metabolic inflammation between primiparous and multiparous Zebu cows during transition period - WANKHADE, PRATIK RAMESH; Ayyasamy, Manimaran; KUMARESAN, ARUMUGAM; SIVARAM, MUNIANDY; SEJIAN, VEERASAMY; RAJENDRAN, DURAISAMY (The Indian Journal of Animal Sciences, 2022)
This study aimed to estimate the changes in the milk yield, milk fat, energy indicators [NEFA, BHBA, Dry Matter Intake (DMI) and Body Condition Score (BCS)] and concentration of innate immune molecules (Haptoglobin: Hp, Serum Amyloid A: SAA, TLR-4, TNF-α, IL-1β, IL-6, and IL-8), during the transition period in primiparous and multiparous dual-purpose zebu (Deoni) cows. The blood sample was collected at weekly intervals during pre-partum (-21±2, -14±1, -7±1, d), date of calving (day 0), and postpartum period (3±1, 7±1, 14±1, 21±2 d) for estimation of the above plasma variables using commercially available bovine specific ELISA kits. DMI and BCS during the corresponding period were also recorded. Data were analyzed using a linear mixed model considering group, time and their interaction as fixed effects. Group, time and their interaction had significant effect on DMI where primiparous cows consumed higher DMI during early postpartum period as compared to multiparous cows. Group alone had significant effect on milk yield, milk fat per cent and BHBA level while time alone influenced BCS. The interaction of group and time had significant effects on plasma TLR-4 and IL-8 concentration. Group also had significant effect on Hp and TNF-α levels. It was concluded that parity had significant effect on metabolic and immune indicators where higher DMI during transition period resulted in more milk yield in primiparous than multiparous indigenous (Deoni) cows.